(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2019)
This paper discusses the views expressed by three colonial women writers, namely Margaret Brooke (The Ranee of Sarawak), Emily Innes and Isabella Bird. By comparing the results of their writings such as My Life in Sarawak (1913) by Margaret Brooke, with Emily Innes’s The Chersonese With the Gilding Off (1885) and Isabella Bird’s The Golden Chersonese and the Way Thither (1883). All three works were written during the era of British colonial rule in Sarawak and Malaya, and are closely linked with the roles of Innes and Bird as the wives of British colonial officers in Malaya, as well as Margaret Brooke’s as the wife of Sarawak’s White Rajah. Taking into consideration the differences in their economic background and status in society as presented by Sara Mills (2002), the viewpoints of these three authors concerning life in the East, the Malays, and their civilisation reveal differences in their perception. This paper tries to show that the views of these three authors are not uniform, homogeneous or ’unified’, and are especially divergent regarding the policies of the British government in Malaya.Keywords: colonial, Sarawak, Ranee, Malay, Sarah Mills